A career in theoretical physics - P.W. Anderson (World Scientific, 1994)
Philip W. Anderson is a theoretical physicist who has been described as the most imaginative of condensed matter physicists working today, or, alternatively, as the "godfather' of the subject. His contributions as often set the agenda for others to work on as they constitute specific discoveries...